Urinary tract infection in children at Victoria Hospital, a district hospital in Cape Town, South Africa - Shepherd, Danielle (Department of Paediatrics and Child Health, 2023)
Background: Urinary tract infections (UTI) are one of the most common bacterial infections in childhood, with the potential to cause acute and long-term complications. Diagnosing UTI in children is often challenging due to non-specific symptoms, difficulty in collecting sterile specimens, and culture results only becoming available after 24-48 hours, necessitating initiation of empiric antibiotic therapy. Recent data on the epidemiology and antibiotic susceptibility profile of community-acquired bacterial UTI in children in Cape Town is lacking. Objectives: To describe the clinical profile and organisms including antibiotic susceptibility testing (AST) results in children <10 years of age with community-acquired, culture-confirmed bacterial UTI attending Victoria Hospital, Cape Town. To compare the AST findings with the current South African (SA) Hospital Level Paediatric Standard Treatment Guidelines (STG) which recommend oral or parenteral amoxicillin/clavulanic acid as first-line empiric treatment for children with UTI, with ceftriaxone included as an alternative for neonates or acutely ill infants. Methods: A retrospective review of medical records and laboratory results of children <10 years of age who had a urine specimen submitted for culture and AST to the National Health Laboratory Service from Victoria Hospital between 1 February 2016 – 31 July 2019 was performed. The study definition of a culture-confirmed bacterial UTI is modified from the SA STG guidelines: (1) any culture from a suprapubic aspirate, (2) culture of >104 colony forming units (CFU)/mL of a single organism from a catheter urine specimen, (3) culture of >105 CFU/mL of a single organism from a mid-stream clean catch specimen or if the urine sampling technique was not indicated in the laboratory or medical records. Descriptive statistics were used to analyse the data. Results: From 528 urine specimens submitted, 89 specimens met the study definition of bacterial UTI and were included in the microbiological analysis. Seventy-eight children with available medical records were included in the demographic and clinical analysis. Median (interquartile range) age was 25 (0;117) months and 58% were female. One or more nonspecific features of systemic illness were reported in 65% of children, and 51% had at least one symptom specific to the urinary system. Enterobacterales accounted for 99% of the organisms cultured (85% were Escherichia coli) and their susceptibility was amoxicillin/clavulanic acid (58%), cefuroxime (84%), third and fourth generation cephalosporins (88%), ciprofloxacin (94%), gentamicin (86%) and nitrofurantoin (90%). Eleven (12%) isolates were extended spectrum beta lactamase-producing organisms but no carbapenem-resistant organisms were isolated. Conclusion: Although this study did not evaluate clinical outcomes of children, the AST finding that only 58% of Enterobacterales isolates were susceptible to the recommended empiric treatment with amoxicillin/clavulanic acid raises the concern that children may not be receiving appropriate treatment for UTI. Further research is needed on the antibiotic susceptibility profile and clinical outcome of children treated for UTI in order to inform appropriate empiric antibiotic treatment recommendations.